2015
DOI: 10.1007/978-3-319-16486-1_27
|View full text |Cite
|
Sign up to set email alerts
|

Managing Academic Profiles on Scientific Social Networks

Abstract: Abstract. This article investigates the way in which communication science researchers use and manage academic social network sites. On this basis, a representative sample of 244 Spanish scholars was selected from the Spanish Association of Communication Researchers, which consists of more than 600 members. This article explores the presence of Spanish communication scholars in two academic networks: ResearchGate and Academia.edu. Furthermore, it examines the way in which researchers are using these platforms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Nature found that just under half of the more than 3,500 scientists and engineers they surveyed visit ResearchGate regularly (Van Noorden, 2014), while a recent survey of over 20,000 respondents by researchers at Utrecht University Library found that 61% who have published at least one paper use ResearchGate Matthews, 2016). Other measures of the proportion of researchers using ResearchGate range from 15% to 65% depending on the population studied (Campos & Valencia, 2015;Haustein et al, 2014;Laakso et al, 2017;Lupton, 2014;Madhusudhan, 2012;Mahajan, Singh, & Kumar, 2013;Meishar-Tal & Pieterse, 2017;Míguez-González, Puentes-Rivera, & Dafonte-Gómez, 2017;Mikki et al, 2015;Ortega, 2015;Singh, 2016;Tran & Lyon, 2017).…”
Section: Researchgatementioning
confidence: 99%
See 1 more Smart Citation
“…Nature found that just under half of the more than 3,500 scientists and engineers they surveyed visit ResearchGate regularly (Van Noorden, 2014), while a recent survey of over 20,000 respondents by researchers at Utrecht University Library found that 61% who have published at least one paper use ResearchGate Matthews, 2016). Other measures of the proportion of researchers using ResearchGate range from 15% to 65% depending on the population studied (Campos & Valencia, 2015;Haustein et al, 2014;Laakso et al, 2017;Lupton, 2014;Madhusudhan, 2012;Mahajan, Singh, & Kumar, 2013;Meishar-Tal & Pieterse, 2017;Míguez-González, Puentes-Rivera, & Dafonte-Gómez, 2017;Mikki et al, 2015;Ortega, 2015;Singh, 2016;Tran & Lyon, 2017).…”
Section: Researchgatementioning
confidence: 99%
“…Nature found that just under half of the more than 3,500 scientists and engineers they surveyed visit ResearchGate regularly (Van Noorden, 2014), while a recent survey of over 20,000 respondents by researchers at Utrecht University Library found that 61% who have published at least one paper use ResearchGate Matthews, 2016). Other measures of the proportion of researchers using ResearchGate range from 15% to 65% depending on the population studied (Campos & Valencia, 2015;Haustein et al, 2014;Laakso et al, 2017;Lupton, 2014;Madhusudhan, 2012;Mahajan, Singh, & Kumar, 2013;Meishar-Tal & Pieterse, 2017;Míguez-González, Puentes-Rivera, & Dafonte-Gómez, 2017;Mikki et al, 2015;Ortega, 2015;Singh, 2016;Tran & Lyon, 2017).A number of studies have reported that ResearchGate is relatively more popular among researchers in the sciences when compared with the academic social network Academia. edu, which is preferred by researchers in the social sciences and especially the humanities Campos-Freire & Rúas-Araújo, 2016;Elsayed, 2015;Jamali et al, 2016;Matthews, 2016;Mikki et al, 2015;Nández & Borrego, 2013;Ortega, 2015;Thelwall & Kousha, 2015;Thelwall & Kousha, 2017;Van Noorden, 2014 Míguez-González et al, 2017;Mikki et al, 2015;Ortega, 2015;Singh, 2016;Tran & Lyon, 2017;Van Noorden, 2014).…”
mentioning
confidence: 99%
“…Elsayed (2015) also found that ResearchGate was preferred by most Arab researchers, and if they had more than one account the second was likely to be on Academia.edu. In contrast, Campos and Valencia (2015) found that Spanish researchers tended to prefer Academia.edu, though they cite another study (Punin, Direito, & Calva, as cited in Campos & Valencia, 2015) which found that many of these profiles contained no content. Meishar-Tal and Pieterse (2018) also found a prevalence for ResearchGate use by Israeli researchers, where they also found that most researchers were using social networking tools for self-promotion and increased discovery.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Academic social networks have been the subject of a fair amount of academic research, given their relatively recent entry into the scholarly communication landscape. A number of studies have been done on the adoption rates by researchers in a particular discipline (Muscanell & Utz, 2017;Marra, 2016;Ortega, 2015;Van Noorden, 2014;Haustein et al, 2014) or a particular country (Mikki, Zygmuntowska, Gjesdal, & Ruwehy, 2015;Campos & Valencia, 2015;Elsayed, 2015;Míguez-González, Puentes-Rivera, & Dafonte-Gómez, 2017;Meishar-Tal & Pieterse, 2017. Mikki et al (2015 found that ResearchGate was used most often by Norwegian scholars overall, though humanities scholars used Academia.edu more frequently.…”
Section: Literature Reviewmentioning
confidence: 99%